Roma triumphans i Parthia capta na Łuku Septymiusza Sewera w Rzymie - Kluczek, Agata (Studia Europaea Gnesnensia, 2012)
The undertaken deliberations concern the so-called triumphal frieze on the Arch of septimius severus in Rome. They are situated on two fundamental planes: the relationship of the relief ’s content with the history of the times of septimius severus and the relationship of the motifs depicted on the relief with the Roman iconographic tradition.